Color prediction in ceramic enamels using the kubelka munk model - Chavarriaga Miranda, Edgar Andrés; Correa Rojas, Nelson Alonso; Montoya Carvajal, Juan Fernando; Restrepo Baena, Oscar Jaime (TECCIENCIA, 2015)
In the present research, the Kubelka-Munk model was applied for predicting color in glazes used in ceramic decoration. The model relates the absorption coefficient, scattering coefficient and the diffuse reflectance expected for a mixture of three ceramic pigments in the visible spectrum. The concentrations of each enamel were also considered making possible predict a particular tone. It was used visible spectrophotometry to obtain the absorption and scattering coefficients of pigments chosen on ceramic substrates for their use in pottery, and also for the diffuse reflectance spectra of mixtures selected for burned enamels. The results showed a good prediction in some regions of the visible spectrum, concluding that the model could be used for quality control of products manufactured in the ceramic industry.